Nghiên cứu lý thuyết tương tác giữa C2H6, CH3CH2F, CH3CHF2, CH2FCHF2 và CHF2CHF2 với H2O - Trung, Nguyễn Tiến; Huế, Trần Thành; Thọ, Nguyễn Minh; Minh Huệ, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
The binding energies of some the complexes (corrected by ZPE and BSSE) range between 0.49 kcal.mol-1 and 2.62 kcal.mol-1. There is a contraction of the CH bond bound to oxygen atom, a blue shift. There is a decrease of the occupation of the σ*(C1H2) and σ*(C1H3) antibonding orbitals in the IIA, IIIB, IV respective complexes performed in the firgure 1. The NBO analysis indicates that the H-index is not a reason for physical nature of improper blue-shifting hydrogen bond in the complexes examined, but the EDT and the increase of s-character of CH bonding are major reasons for the contraction. The data obtained in this work allow us to establish the following correlations between the frequency shifts of the stretching vibrations  and variations of the corresponding bond lengths: ∆ν(C-H) = -12956 ∆r(C-H) +2,086 (1), ∆ν(O-H) = -13349 ∆r(O-H) + 10,725. We also have deduced the correlation: ∆r(O-H) = 2.5075∆σ*(O-H) -0.0026